PENERAPAN MODEL PETA KONSEP TIPE NETWORK TREE MENGGUNAKAN MEDIA GAMBAR UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA MATA PELAJARAN IPA KELAS IV SDN 3 JANGKAR KABUPATEN SITUBONDO TAHUN PELAJARAN 2015/2016 - Eko Hadi Purwanto (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2016)
The model of concepts map network tree type is a way to show the natural science subject’s concepts and proposition. While, media image is everything in visual form which is transform into 2 shapes of dimension as the result of thoughts such as painting, portrait, slide, film, strip, opaque, and projector. The subject of this research are pupils grade IV, uneven semester of public primary school SDN 3 Jangkar, district Situbondo which consist of 21 pupils, 12 girls and 9 boys. Type of this research is classroom action research. It is measured by the ARCS motivation questionnaire. The cycle I is average of ARCS pupil’s motivation aspect of 2,34 which is categorized as quite good. The cycle II is average of ARCS pupil’s motivation aspect is 2,92 which is categorized good. The increasing of ARCS’s motivation is 0,58. The increasing from cycle I to cycle II is 8,81% and the complexness is 28,57%. Based on the analysis result it can be conclude that the application model of map concept learning type network tree by using image media is able to increase the motivation and learning outcome of the pupils of grade IV, public primary school of SDN Jangkar district of Situbondo